Konstruksi Ilmu Ma’ani al-Hadis Kaum Kontekstualis - Ahmad Muttaqin (Farabi, 2016)
Understanding the hadith is the most important step after examing its authenticity. The aim of this paper is to explain the development history of ma’ani> al-h}adi>s\ and to analyze the comtemporary methods from five thinkers namely: Fazlur Rahman, Yusuf Qardhawi, Muhammad al-Ghazali, Syuhudi Ismail and Khaled M. Abou El Fadl. This concludes that the prosess of understanding hadis (ma’ani> al-h}adi>s\) has been developed by many Islamic scholars from classical era to contemporary era. Analyzing the ways of ma’a>ni al-h}adi>s\of five thinkers above, are able to be classified into three steps; analyzing the text, historical context (micro and macro-asba>b al-wuru>d), and applying in reader’s context.